Effect of Work Motivation and Professional Competence about the Performance of Teachers in SMP N Tebing Tinggi, Meranti Islands Regency - Erna Lestari Rambe; Dedi Nofrizal (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the effect of work motivation on teacher performance, the effect of professional competence on teacher performance at State Middle School Tebing Tinggi District, Meranti Islands Regency, Riau Province. The research uses a quantitative approach with a simple random sampling technique with the intention that each subject has the same opportunity to be sampled. The population of this study were all teachers who taught at State Junior High Schools in Tebing Tinggi District, consisting of 52 teachers. Data collection techniques are by questionnaire, observation and documentation. The results of this study indicate that: 1) There is a positive and significant influence between work motivation on teacher performance as indicated by the results of the t test obtained by a tcount of 4.455 greater than the ttable value of 1.671 at a significance level of 5% with a determinant coefficient of 0.284 so that it can be concluded teacher performance is influenced by work motivation by 28.4% while 71.6% teacher performance is influenced by other variables that cannot be explained in this study. 2) There is a positive and significant influence between professional competence on teacher performance as indicated by the results of the t test obtained by a tcount of 5.857 greater than the ttable value of 1.671 at a significance level of 5%, with a determinant coefficient of 0.407 so it can be concluded that teacher performance is influenced by competence professionalism of 40.7% while 57.3% of teacher performance is influenced by other variables that cannot be explained in this study. 3) There is a jointly positive and significant influence between work motivation and professional competence on teacher performance as indicated by the results of the F test, namely the value of Fcount > Ftable (21.729 > 3.190) at a significance level of 5%